2011
DOI: 10.1016/s0140-6736(11)60649-1
|View full text |Cite
|
Sign up to set email alerts
|

Trends in selective abortions of girls in India: analysis of nationally representative birth histories from 1990 to 2005 and census data from 1991 to 2011

Abstract: Summary Background India's 2011 census revealed a growing imbalance between the numbers of girls and boys at ages 0–6 years, which we hypothesise is due to increased prenatal sex determination followed by selective abortion of female foetuses. Methods We examined sex ratios by birth order among 0.25 million births in three rounds of the nationally-representative National Family Health Survey covering the period from 1990 to 2005. We estimated totals of selective female abortion by examining the birth cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
216
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(227 citation statements)
references
References 12 publications
10
216
0
1
Order By: Relevance
“…On a contrary, a study conducted by Jha et al showed, the decline in conditional sex ratio for second-order births when the first born was a girl were much greater in mothers with 10 or more years of education than in mothers with no education, and in wealthier households compared with poorer households. 11 Whereas, no decline was detected in sex ratio for second order births if the first born was a boy. In our study, increase in the awareness about the PCPNDT Act and the immorality of gender selection may be a reason among the literate and economically sound women for not disclosing son preference.…”
Section: Discussionmentioning
confidence: 89%
“…On a contrary, a study conducted by Jha et al showed, the decline in conditional sex ratio for second-order births when the first born was a girl were much greater in mothers with 10 or more years of education than in mothers with no education, and in wealthier households compared with poorer households. 11 Whereas, no decline was detected in sex ratio for second order births if the first born was a boy. In our study, increase in the awareness about the PCPNDT Act and the immorality of gender selection may be a reason among the literate and economically sound women for not disclosing son preference.…”
Section: Discussionmentioning
confidence: 89%
“…Past research indicates that stated son preferences from NFHS-1 match state-level sex ratios from the 1990 Indian census (Bhat, Mari, and Zavier 2003). However, stated son preferences have started to fall in recent history (Retherford and Roy 2003), while sex ratios remain skewed towards males (Jha et al 2011). …”
Section: Stated Son Preference Outcomementioning
confidence: 99%
“…The combination of increasingly prevalent sex-selective abortion technologies and increasing resources of a rising middle class allows more Indian women to select out of having daughters, even though social norms concerning son preference are weakening (Kashyap and Villavicencio 2016;Jha et al 2011;Arnold, Kishor, and Roy 2002;Retherford and Roy 2003). Thus, changes in stated son preferences might reflect the start of long-standing social processes that will eventually translate into declining sex ratios in India.…”
Section: Stated Son Preference Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…We have also stated that selective feticide concerns only 2-4% of pregnancies carrying a girl, but the numbers are large in absolute terms. 3 It is therefore unfortunate that Dalal et al 1 are offended by some of these statements. The statements in our review are amply supported by references to the vast number of papers and books published on the subject, 70% of which report work carried out in India by Indian authors.…”
mentioning
confidence: 99%